PENYALAHGUNAAN KONSEP KAWIN MUT’AH PADA PRAK- TIK KAWIN KONTRAK - Abdullah, Zaitun; Tridewiyanti, Kunthi (Journal of Islamic Law Studies, 2021)
Marriage is an emotional and physical bond between a man and a woman to establish a perpetual family as stipulated in The Marriage Act Number 1 Year 1974 and The Islamic Law Compilation (Kompilasi Hukum Islam). However, there are facts that in Tugu Utara Village (Desa), Cisarua, Bogor, many couples conduct marriage just for temporary period. That marriage known as the con- tract marriage (perkawinan kontrak), and people who live in Tugu Utara Village call it with mut’ah marriage. Of course, that is an interesting matter to study, because it seems there is a mistake in un- derstanding the concept of mut’ah marriage. By conducting non-doctrinal research, this research will show that the people’s perception in Tugu Utara Village about contract marriage, which is consid- ered same as mut’ah marriage, is totally wrong. The inaccuracies are due to, among others, couples who have conducted contract marriage are not the followers of Shiite, and also, in some points, the marriage contract was in fact very different from the real mut’ah marriage practice. Besides that, the contract marriage, which is conducted in Tugu Utara Village, in many aspects is unlawful.